Influência de diferentes substâncias químicas auxiliares na resistência de união de cimentos endodônticos à base de metacrilato à dentina radicular - Fuzinatto, Roger Nicolini (2014)
The aim of this study was to evaluate the bond strength of two methacrylate-based endodontic sealer, Real Seal SE (Sybron Dental Specialties, Orange, CA, USA) and EndoREZ (Ultradent Products Inc., South Jordan, UT, USA) to root dentin treated with different auxiliary chemical substances. Sixty single-rooted human teeth were used. The chemical-mechanical preparation was performed with rotary nickel-titanium instruments ProTaper until F5 instrument. The samples were treated with the different auxiliary chemicals, as follows: G1 (control): physiological saline, G2: 5.25% sodium hypochlorite (NaOCl) + 17% EDTA; G3: NaOCl + 17% EDTA + 95% ethanol, G4: 2% chlorhexidine gel (CHX) + 17% EDTA; G5: CHX +17% EDTA + 95% ethanol. Each group was randomly divided into two subgroups, in one of them EndoREZ cement was used and in the other Real Seal SE. Once obtured, the roots were cut and the push-out test was conducted. For statistical analysis was conducted the two-factor ANOVA (cement and surface treatment) with a significance level of 5%. Regarding the comparison between failures of cements, was held the Chi-square test to verify the association between experimental groups and the type of failure observed. The results have shown that the highest values of bond strength were in groups prepared with CHX and ethanol and obtured with the Real Seal SE sealer; in groups where NaOCl was used, values of bond strength were lower for the same type of sealer. To EndoREZ sealer the NaOCl did not decrease the bond strength values compared to control group, however that was used CHX had better results It can be concluded that the auxiliary chemical substance used in the preparation of root canals interferes with the values of bond strength of both Real Seal SE and EndoREZ sealer